Ta’dhir in Islamic Law : Types of Crimes and Punishments - Mukhtor Akramov (Penerbit Jurnal Indonesia, 2024)
This article analyzes the linguistic and terminological meanings of the term “ta'zir” and its application as a form of criminal punishment in Islamic law. The role of ta'zir in the Quran is examined, along with the different views expressed by various Islamic jurists, including Abu Yusuf, Imam Azam, and other legal scholars. The article discusses how ta'zir punishments are specific penalties assigned for various actions, such as insults, slander, and psychological harm, among others. It also outlines that ta'zir penalties are imposed for crimes that do not reach the level of hudud or expiation and can take various forms, such as warnings, lashes, or fines.